A study to assess the role of modified biophysical profile in prediction of perinatal outcome in high-risk pregnancy - Nayak, Kundan Singh; Gaur, Sindhu Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: High-risk pregnancies are associated with increased maternal and fetal morbidity and mortality, particularly in resource-limited settings. Effective antenatal surveillance is critical for improving outcomes, and the Modified Biophysical Profile (MBPP) has emerged as a practical tool due to its simplicity and reliability. This study aimed to assess the diagnostic value of MBPP in predicting adverse perinatal outcomes in high-risk pregnancies and to use it a primary surveillance tool. Methods: A prospective observational study was conducted at SMS Medical College, Jaipur, from July 2023, involving 200 high-risk pregnant women (≥32 weeks gestation). MBPP, comprising non-stress test (NST) and amniotic fluid index (AFI), was used to monitor fetal well-being. Outcomes such as mode of delivery, APGAR scores, NICU admissions, and neonatal complications were evaluated. Statistical analysis was performed to determine the predictive performance of MBPP, NST, and AFI. Results: Out of the 200 cases, 63% underwent caesarean delivery. Abnormal MBPP was observed in 54% of cases and was significantly associated with fetal distress, NICU admissions, and low APGAR scores. MBPP showed high sensitivity and accuracy in predicting adverse outcomes, outperforming AFI and being comparable to NST. Anemia (26%), previous caesarean (20%), and oligohydramnios (18.5%) were the most common risk factors. Respiratory distress (45.5%) was the leading cause of NICU admission. Conclusions: MBPP is a reliable, non-invasive, and cost-effective screening method for high-risk pregnancies, aiding in early detection of fetal compromise and timely intervention to improve perinatal outcomes.